Virus de inmunodeficiencia humana y transfusión sanguínea - Larrondo, Milton (Revista Hospital Clínico Universidad de Chile, 1997)
Human lnmunodeficiency Virus ( HN) and blood transfusions The infections with HIV-1 related to blood transfusions in Chile and in the Blood Bank of the J.J. Aguirre Clinical Hospital is reviewed among blood donors prior to screening, with special attention to haemophiliac patients. The risk of AIDS related to blood transfusions is actually very low, and there are any case of chilean haemophiliacs infected with cryoprecipitate or plasma.